Digitalisasi Administrasi Publik: Analisis Kesiapan Regulasi dalam Mendukung Percepatan Pembangunan Nasional - Annisa Ostha Hamra; Azzahra Nadifa; Aril Maulana (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The problem of this research is the extent to which the existing regulatory framework is able to support the acceleration of the digitalization of public administration in Indonesia and the structural obstacles that hinder its implementation. This research aims to describe the legal environment of digitization of public administration, assess the consistency of existing regulations, identify institutional challenges and implementation capacity, and provide contextual policy recommendations. The type of research used is qualitative descriptive with data collection techniques through systematic literature studies of regulatory documents, official policies, evaluation reports, and academic literature. The analysis was carried out using the content analysis method and comparative policy analysis with the framework of the Marchetti (2021) regulatory readiness model modified for the Indonesian context, and validity was maintained through triangulation of data sources from official regulations, academic reports, and assessments of international institutions. The article concludes with policy recommendations encompassing enhancing cross-ministerial coordination, accelerating digital literacy amnesia, and improving cross-ministerial cooperation. The results show that, although SPBE regulations provide an adequate foundation, organizational fragmentation, lack of human resource capabilities, and digital infrastructure disparities continue to be significant obstacles to equitable implementation. The article ends with policy suggestions that include better cross-ministerial coordination, more civil servants' digital literacy, and more infrastructure networks to remote and poor areas